Pengaruh Partisipasi Anggaran, Komitmen Organisasi, Penekanan Anggaran, Locus Of Control, Dan Kohesivitas Kelompok Terhadap Timbulnya Kesenjangan Anggaran Pada SKPD Pemerintah Provinsi Riau - Intan Permanasari; Zulbahridar '; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to investigate the effect of budget participation, organization commitment, budget emphasis, locus of control, and group cohesiveness on budgetary slack. The subject of this study are echelon III and IV in 38 institutions in the district Government of Riau. The data was collected by distributing questionnaires to 152 respondents, but only 142 respondents who fill out the questionnaires. The analysis tool used is multiple regression using SPSS program version 17.0 The results show that budget participation, organization commitment, budget emphasis, locus of control, and group cohesiveness have siginificant effect and positive impact on budgetary slack. Based on the resultsKeywords : Budget Participation, Organizational Commitment, Budget Emphasis, Locus of Control, Group Cohesiveness, and Budget Slacks